CLASSIFICATION OF WASTE ELECTRICAL AND ELECTRONIC EQUIPMENT BY ECOLOGICAL HAZARD - BUCHKA, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article discusses the problem of waste electrical and electronic equipment, which is constantly growing due to the mass consumption of equipment and its rapid obsolescence. Data on the volumes and forecasts of e-waste generation in the future, which belong to specific types of waste based on their composition and structure, are provided. The article emphasizes that due to the content of various components made of different materials, including rare, valuable, and hazardous compounds, waste electrical and electronic equipment poses a significant threat to human health and the environment. As a result, there is a need for specialized management of this type of waste. Based on the analysis of the characteristics and properties of the waste, aiming to ensure effective management of this waste and focusing on its ecological hazards, a classification of waste electrical and electronic equipment by ecological hazard is proposed. The proposed waste classification divides them into three categories, depending on the level of potential negative impact on human health and the environment as a result of improper handling, and determines optimal management methods for each category. It is noted that this classification can be used as an auxiliary tool in the 10R waste management hierarchy, which is the basis of the circular economy 3.0, and is described in detail in the article in the context of this type of waste. A separate part of the article is dedicated to comparing the proposed classification of waste with other known classifications of waste electrical and electronic equipment. Both common features and differences are highlighted, emphasizing the greater comprehensiveness of the proposed classification, including the determination of optimal methods for of e-waste management to reduce the negative impact on the environment and extend the life cycle of the equipment.